Personified vulva, ritual obscenity, and Baubo - Karatas, Aynur-Michèle-Sara (Journal of Greek Archaeology, 2019)
Several clay figurines dating to the Hellenistic period from the sanctuaries of Demeter at Priene and Samos depict the lower part of naked female bodies with arms and legs (Figures 1–2). The facial features are represented on the stomach of the figurines. One single clay figurine from Erythrai and two from the sanctuary of Demeter at Mytilene represent the facial features on the stomach without arms and legs (Figure 3). The iconography of the clay figurines recalls the obscene gesture of Iambe, who lifted up her skirt and exposed her genitals (Hom. Hymn Dem. 199–205). The obscene act of Iambe offered an explanation for ritual mockery. Depending on the festival, ritual mockery was performed by men and women, or only by women. Despite the significance of ritual mockery for the Eleusinian cult, Iambe/Baubo is only mentioned in a few inscriptions dedicated outside Attica. The present paper aims to analyse the so-called clay figurines of Baubo. Before discussing the clay figurines, I will first reconsider the written sources on Iambe and Baubo dating to the Archaic and later periods. Given the fact that several papers discuss most written sources on Baubo, ritual mockery, and lifting up the skirt, I will focus on selected written sources on Baubo and ritual mockery performed at the festivals of Demeter.